Pengaruh Pendekatan Sains Teknologi dan Masyarakat terhadap Literasi Sains Peserta Didik Kelas VII MTs YMPI Rappang - Mutiah Muthmainnah; Ramlawati Ramlawati; Hasanuddin Hasanuddin (Celebes Science Education, 2023)
This study aims to find out: (1) improvement in scientific literacy of seventh grade students who are taught with the STS approach and conventional approach, (2) the effect of the STS approach to the scientific literacy of seventh grade students. This research is a Quasi Experimentalusing a Non-equivalent Control Group Design. The study population was all students of seventh grade at MTs YMPI. Sampling through purposive sampling technique and obtained VII E as an experimental class and VII D as a control class. The research instrument of learning outcomes test in the form of multiplechoice questions totaling 25 items. Data collection techniques in this study were by giving pretest and posttest. Data analysis was performed using descriptive analysis and inferential analysis. The results of descriptive analysis are known that ability of scientific literacy in the experimental class taught using the STS approach obtained an average score of N-gain of 0.66 in the medium category and in the control class that was learned without using the STS approach of 0.48 in the medium category. The results of the inferential analysis obtained using the t-test (hypothesis test) showed that H0 was rejected and H1 was accepted, so it can be concluded that the STM approach had an effect on improving the ability of scientific literacy student of seventh grade at MTs YMPI Rappang on subject matter Energy in the Living System.